Syngas exploitation from novel catalytic steam reforming of palm oil mill effluent over lanthanum nickel trioxide - Y. W., Cheng; K. H., Ng; Cheng, C. K. (Universiti Malaysia Pahang, 2018)
The exhaustion of fossil fuels is foreseen with the increasing world energy demand that provoked by substantial growth of world’s population. To address this issue, numerous viable renewable energy resources had been utilized, viz. solar, wind, geothermal, tidal, and biomass energies by virtue of their abundance and green approach. Differ from other renewable energies, biomass energy is qualified to be the true surrogate for fossil fuels since it offers a waste to energy approach that unbounded by climatic, seasonal, and regional constraints. In a steam reforming process, the biomass which are carbonaceous substances can be thermally converted into combustible gaseous products primarily syngas, via oxidation with steam at elevated temperature [1]. Essentially, syngas become attractive due to its wide applications, viz. synthetic fuel for energy generation and chemical intermediates for many downstream chemicals such as methanol, hydrogen, and acetic acid [2].